STRATEGI EVAKUASI DALAM MEMBANGUN KETANGGUHAN BENCANA TSUNAMI PADA FASILITAS INDUSTRI KOTA CILEGON - Firzat Shindi, Mohammad; Fadilah Ramadhan, Fardhi; Annisa Fitri, Zahra (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The city of Cilegon is located in the province of Banten, situated at the western tip of Java Island and serving as a connecting area between Java and Sumatra. It plays a crucial role in the development of national strategic industries. Additionally, Cilegon faces a high level of disaster risk, particularly from the threat of tsunamis along its coastal areas bordering the Sunda Strait, as well as high vulnerability to industrial disasters. Therefore, an effective evacuation strategy is being implemented as part of efforts to build resilience against disasters. This research adopts a quantitative approach, utilizing scoring methods to determine the final outcomes. The technical approach involves using ArcGIS software to aid in scoring processes through Attribute Tables, resulting in spatial maps such as tsunami hazard maps, collateral hazard maps, and evacuation plan maps. Subsequently, disaster risk reduction strategies will be formulated. Four districts in Cilegon are affected by tsunamis: Ciwandan, Citangkil, Grogol, and Pulomerak. Ciwandan and Citangkil districts have a high tsunami hazard index, while Grogol and Pulomerak districts have a moderate hazard index, with Pulomerak district having the highest inundation area. The largest submerged industrial facilities include parking lots and warehouses, with a total submerged industrial area of approximately 329 hectares. The Estimated Time of Evacuation (ETE) exceeds the Estimated Time of Arrival of the Tsunami Evacuation Wave (ETA-TEW) in several districts, namely Ciwandan, Grogol, and Pulomerak. Citangkil, Grogol, and Pulomerak districts still lack evacuation places, so six new evacuation locations are planned in Cilegon city.